Gene Therapy of Cancer
DOI: 10.1385/1-59259-086-1:537
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated Wild-Type p53Gene Transfer into Head and Neck Cancers

Abstract: Mutation of the p53 tumor-suppressor gene is recognized as one of the most common genetic alterations in human malignancy to date (1). Approximately 60% of human tumors are thought to possess mutation at the p53 locus. Transient overexpression of the wild-type p53 gene in various malignancies has been considered a potential molecular intervention strategy (2 -7). This strategy is based on the role that wild-type p53 plays as a tumor-suppressor gene and inducer of cell-cycle arrest and apoptosis (1 ,8-11).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0
1

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 6 publications
1
77
0
1
Order By: Relevance
“…Expression of the gene product is transient and phase I clinical trials have shown the virus to be safe and well tolerated at the highest doses of 10 11 PFU. [67][68][69][70][71][72][73] Studies have demonstrated the feasibility of both intravascular 74 and intratumoral 75 administration.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the gene product is transient and phase I clinical trials have shown the virus to be safe and well tolerated at the highest doses of 10 11 PFU. [67][68][69][70][71][72][73] Studies have demonstrated the feasibility of both intravascular 74 and intratumoral 75 administration.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I and phase II trials using a recombinant p53 adenovirus (Ad-p53) demonstrated little toxicity and encouraging results in the adjuvant setting. 15 In combination with chemotherapy, several trials have administered a replication-selective adenovirus (ONYX-015) designed to preferentially replicate in and lyse p53-deficient cancer cells while sparing normal cells. 16,17 These phase II studies demonstrated objective responses at the site of injection, in patients with multiple lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the functions of the mda-7 gene and its downstream pathways remain unknown. Consequently, to understand better how mda-7 functions and to help broaden the scope of current anticancer gene therapy strategies, [7][8][9] we tested the antitumor effects of a novel adenoviral vector carrying the mda-7 gene (Admda-7) on non-small cell lung cancer lines and investigated the underlying mechanisms of tumor killing.…”
Section: Introductionmentioning
confidence: 99%